Ewolucja karty polaka jako instrumentu polityki państwa - Marcin Gońda (University of Warsaw, Centre of Migration Research (CMR), 2022)
– The aim of the paper is to present the evolution of the Pole's Card as an instrument of state policy that took place over the last fifteen years. The Card was addressed at the time of its introduction in 2007 to people of Polish origin in the successor states of the USSR but from 2019 it is targeted at Poles from all over the world. First, the paper describes amendments to the provisions of the Act on the Pole's Card and, second, it discusses the political narratives that accompanied the works on these provisions in the Polish Parliament. The presented analyses indicate that while initially the Pole's Card was a tool of diasporic policy aimed at maintaining relations with people of Polish origin living beyond the Eastern border of Poland (mainly in Lithuania, Belarus and Ukraine), it has transformed over time into an instrument of migration policy, which is intended to facilitate the arrival and settlement on the territory of Poland and the acquisition of Polish citizenship.
Keywords: 330; the Pole’ s Card; ethnic card; diaspora; diasporic policy